The challenge of constitutional transformation of society through judicial adjudication: Mildred Mapingure v Minister of Home Affairs and Ors SC 22/14. - Tsabora, James (Midlands State University, 2016)
The adoption of a new Constitution in Zimbabwe in 2013 to replace the Lancaster House Constitution of 1979 potentially represents an important milestone in the country’s legal history, and also, in the evolution of Zimbabwe as a constitutional democracy. Most importantly, the new Constitution sets an interesting platform for the transformation of society through judicial activism, adjudication and constitutional interpretation and also through the realignment of the country’s laws by the government. Such transformation is necessary in the progressive development of Zimbabwe as a constitutional state.1 This is particularly true considering the fact that the previous 1979 Lancaster House Constitution succeeded in signaling the dawn of political independence in Zimbabwe and putting a break to generations of colonialism, racial domination and oppression. The 2013 Constitution is therefore yet another step in the advancement of the ideals of a constitutional and democratic state and its adoption is a cause for optimism, in the least.